KELAYAKAN FINANSIAL PENGEMBANGAN USAHA PERIKANAN PELAGIS KECIL DI PERAIRAN UTARA NANGGROE ACEH DARUSSALAM (Financial Elegibility to Development of Small Pelagic Fishing in North Territorial Water of Nanggro Aceh Darussalam) - Raihanah Raihanah; Sugeng Hari Wisudo; Mulyono S. Baskoro; Dedy H. Sutisna (Institut Pertanian Bogor, 2011)
Management of small pelagic fishing unit not yet used better in north territorial water of NAD, especially after tsunami. This research aim to analyze financial elegibility of small pelagic fishing unit. The method of research are analysing of invesment, operating cost, benefit, NPV, B/C Ratio, IRR, and ROI. Invesment of drift gillnet (JIH), set gillnet (JIT), loop gillnet (JL), shrimp net (JK), trammel net, fish seine, payang, beach seine, and purse seine are each Rp 523.800.000, Rp 439.000.000, Rp 368.500.000, Rp 284.700.000, Rp 120.350.000, Rp 451.900.000, Rp 426.000.000, Rp 379.100.000, and Rp 1.031.800.000. Solar is dominant operational supporting of small pelagic fishing om location, reaching 60-75 % from total operational cost. Purse seine and drift gillnet have the best of benefit, each Rp 3.812.355.000 per year and Rp 2.536.456.000 per year. Fishing unit can be developed competently each drift gillnet (JIH), set gillnet (JIT), shrimp net (JK), trammel net, fish seine, payang, beach seine, and purse seine. But loop gillnet (JL) is not competent to developed becauce it has IRR -4,36 % (standard > 6,25 %) and B/C ratio 0,97 (standard > 1)